LncRNA NRON down-regulates lncRNA snaR and inhibits cancer cell proliferation in TNBC. Issue 5 (14th May 2019) - Niu, Limin; Fan, Qingxia; Yan, Min; Wang, Liuxing
Abstract : NRON mediates the degradation of tat protein to participate in HIV-1 infection. Interestingly, our study observed the down-regulation of NRON in triple-negative breast cancer (TNBC) tissues compared with paired adjacent healthy tissues. In contrast, lncRNA snaR was up-regulated in TNBC tissues and was inversely correlated with NRON. Expression levels of snaR increased, while expression levels of NRON decreased along with the increase of clinical stages. The snaR overexpression resulted in promoted cancer cell proliferation but did not significantly affect NRON expression. NRON overexpression inhibited cancer cell proliferation and down-regulated snaR. The snaR overexpression reduced the effects of NRON overexpression. We therefore conclude that NRON may down-regulate lncRNA snaR to inhibit cancer cell proliferation in TNBC.